Consensus on a video analysis framework of descriptors and definitions by the Rugby Union Video Analysis Consensus group. Issue 10 (20th February 2020) - Hendricks, Sharief; Till, Kevin; den Hollander, Steve; Savage, Trevor N; Roberts, Simon P; Tierney, Gregory; Burger, Nicholas; Kerr, Hamish; Kemp, Simon; Cross, Matthew; Patricios, Jon; McKune, Andrew J; et al.
Abstract : Using an expert consensus-based approach, a rugby union Video Analysis Consensus (RUVAC) group was formed to develop a framework for video analysis research in rugby union. The aim of the framework is to improve the consistency of video analysis work in rugby union and help enhance the overall quality of future research in the sport. To reach consensus, a systematic review and Delphi method study design was used. After a systematic search of the literature, 17 articles were used to develop the final framework that described and defined key actions and events in rugby union (rugby). Thereafter, a group of researchers and practitioners with experience and expertise in rugby video analysis formed the RUVAC group. Each member of the group examined the framework of descriptors and definitions and rated their level of agreement on a 5-point agreement Likert scale (1: strongly disagree ; 2: disagree ; 3: neither agree or disagree ; 4: agree ; 5 : strongly agree ). The mean rating of agreement on the five-point scale (1: strongly disagree ; 5: strongly agree ) was 4.6 (4.3–4.9), 4.6 (4.4–4.9), 4.7 (4.5–4.9), 4.8 (4.6–5.0) and 4.8 (4.6–5.0) for the tackle, ruck, scrum, line-out and maul, respectively. The RUVAC group recommends using this consensus as the starting framework when conducting rugby video analysis research. Which variables to use (if not all) depends on the objectives of the study. Furthermore, the intention of this consensus is to help integrate video data with other data (eg, injury surveillance).